PROFIT VERSUS INSOLVENCY IN ROMANIAN ECONOMY - GABRIELA CORINA SLUSARIUC; ANCA JAMILA GUŢĂ (Annals of the University of Petrosani: Economics, 2010)
The recession has affected a proportion of 6-7% in Romania, whichconfronted with the consequences of current deficit and sizable debts in foreign currency.Under these circumstances, Romanian companies faced big difficulties, therefore just a littlepart of them managed to reach their target - to get profit. Most of the companies are recordinglosses, and are in insolvency procedure.